A spatial panel wage curve for Spain - Ramos, R; Nicodemo, C; Sanromá, E (Springer Berlin Heidelberg, 2014)
Most empirical studies on the Spanish wage curve have ignored the possible spatial interaction effects between the regions. This paper reconsiders the Spanish wage curve using more recent data than previous studies and taking into account the role of regional spillovers. From a methodological perspective, we apply the two-step procedure proposed by Bell et al. (2002) to estimate a dynamic wage curve with spatial spillovers. In a first stage, we use microdata from the Spanish Social Security Records (Muestra Continua de Vidas Laborales) to obtain composition-corrected wages that are used in a second stage to estimate a wage curve over the period 2000-2010 allowing for spatial effects of unemployment across regions. Opposite to previous studies, we find that the wage equation is highly autoregressive and that regional spillovers are relevant to explain the relationship between unemployment and wages in the Spanish provinces. © 2014 Springer-Verlag Berlin Heidelberg.